2020
DOI: 10.3390/met10070971
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Assisted Sintering Using Heat Converted from Mechanical Energy

Abstract: A new sintering method, namely ultrasonic assisted sintering (UAS), has been proposed using mechanical heat converted from high frequency motion between particles. Pure aluminum specimens with diameter of 5 mm and thickness of ~2 mm have been successfully sintered in two seconds. Based on the thermodynamic analysis, the underlying heating mechanism is quantitatively interpreted, which involves high-frequency interparticle friction and plastic deformation driven by ultrasonic squeezing. Consequently, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Of course, higher values of this ratio should also drive junction growth and densification. This appears to have been the case in the work on ultrasonic compaction of Al powders by Liu et al, [ 68 ] where we estimate σ¯normalc/ H was 0.1 at the onset of junction growth.…”
Section: Mechanisms Of Junction Growth Jamming and Densificationsupporting
confidence: 72%
See 2 more Smart Citations
“…Of course, higher values of this ratio should also drive junction growth and densification. This appears to have been the case in the work on ultrasonic compaction of Al powders by Liu et al, [ 68 ] where we estimate σ¯normalc/ H was 0.1 at the onset of junction growth.…”
Section: Mechanisms Of Junction Growth Jamming and Densificationsupporting
confidence: 72%
“…2D finite element simulations on the ultrasonic compaction of a stack of wires revealed uniform heating within the charge, as well as thermal softening and resulting densification. [ 4 ] In separate work on ultrasonic compaction of Ti‐base metallic glass powder by Chen et al [ 3 ] and aluminum powder by Liu et al, [ 68 ] interparticle junction growth was attributed to thermal softening from transient flash heating events at particle contacts, as one particle is sheared past another. These authors used a simple frictional heating model to estimate flash heating temperature increments in the range 200–400 K for Ti powder and ≈100 K for pure aluminum, which they argued was sufficient to enable the growth of strong interparticle junctions.…”
Section: Mechanisms Of Junction Growth Jamming and Densificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al reported the formation of interfacial Al–Cu ICs via cold rolling [ 18 ]. According to their report, the dislocations accumulated near the interfaces owing to compaction pressure weakened the inter-atomic bonding forces between the individual Al (or Cu), leading to their higher diffusivity [ 27 , 28 ]. Thus, it was concluded that in the present work, the ICs in the Al–Cu composites sintered at approximately 100 MPa were formed via thermal diffusion, but those in the Al–Cu composites sintered at 200–250 MPa were formed via deformation.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic techniques have widely been used for molten alloy material preparation and heat treatment [14][15][16][17][18][19]. However, ultrasonic-assisted sintering techniques are only available at a few hundred degrees Celsius in the current studies [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%